FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KELAPA (COCOS NUCIFERA L) DI INDONESIA - Rahmad Hamdani; Supristiwendi, Supristiwendi; Faoeza Hafiz Saragih (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
This research was conducted to find out and analyze the Factors Influencing Coconut Exports in Indonesia. In this study the type of data used is secondary data. The data analysis used in this study is multiple linear regression analysis with a total of 31 time series data from 1991-2021 which will be used as a research object with HS code 08011200. In this study the independent variable used was coconut production Indonesia, world coconut prices and the rupiah exchange rate. Meanwhile, the dependent variable is the volume of coconut exports in Indonesia. The data used in this study were obtained from various sources including the Food and Agriculture Organization, the Directorate General of Plantations, the International Trade Center, and the Central Bureau of Statistics (BPS). Based on the analysis that has been done, in this study the results showed that the Indonesian coconut production variable (X1) had a positive and not significant effect on the volume of coconut exports in Indonesia. Meanwhile, the world coconut price variable (X2) has a positive and significant effect on the volume of coconut exports in Indonesia and the rupiah exchange rate variable (X3) has a positive and significant effect on the volume of coconut exports in Indonesia